2010
DOI: 10.1007/s10344-010-0388-7
|View full text |Cite
|
Sign up to set email alerts
|

On the efficiency of using song playback during call count surveys of Red-legged partridges (Alectoris rufa)

Abstract: Successful management practices for declining bird species depend often on long-term surveys acquired by point counts. Despite high standardization of field protocols, uncertain detection probability remains an important source of variability and bias in point-count data. This effect is of main importance in low-responsive species as the Red-legged partridge (Alectoris rufa), but it can be counterbalanced, increasing detection probability. In this 2-year study, we sampled using traditional point-count methods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…We demonstrated that distance sampling paired with call-response surveys provided an efficient means of monitoring elusive, non-individually identifiable, and wide-ranging mammalian carnivores with more certainty than has been previously available. This approach is also applicable to species as diverse as squirrels (Downey et al 2006, Tamura et al 2013, foxes (Darden et al 2003), raptors (Mosher et al 1990, McLeod andAndersen 1998), marsh birds (Hinojosa-Huerta et al 2002, Rehm andBaldassarre 2007), game birds (Evans et al 2007Jakob et al 2010, and primates (Urbani 2006, Bezerra et al 2010) provided that their behavior in response to call elicitation is either well known or can be quantified to ensure distance sampling assumptions are reasonably met.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that distance sampling paired with call-response surveys provided an efficient means of monitoring elusive, non-individually identifiable, and wide-ranging mammalian carnivores with more certainty than has been previously available. This approach is also applicable to species as diverse as squirrels (Downey et al 2006, Tamura et al 2013, foxes (Darden et al 2003), raptors (Mosher et al 1990, McLeod andAndersen 1998), marsh birds (Hinojosa-Huerta et al 2002, Rehm andBaldassarre 2007), game birds (Evans et al 2007Jakob et al 2010, and primates (Urbani 2006, Bezerra et al 2010) provided that their behavior in response to call elicitation is either well known or can be quantified to ensure distance sampling assumptions are reasonably met.…”
Section: Discussionmentioning
confidence: 99%
“…As shown for other species (e.g. Jakob et al 2010) taking detection biases into account should not be neglected for wildfowl surveys because it is likely to improve the results from such studies (e.g. Pagano and Arnold 2009) as well as making management policies more appropriate.…”
Section: Discussionmentioning
confidence: 97%
“…Point count surveys have also been modified by some researchers to include playback of recorded bird songs or calls in an attempt to increase detection rates. Species‐specific surveys of songbirds have taken advantage of response to playback of the target species’ vocalizations with mixed success (Sliwa and Sherry , Kubel and Yahner , Jakob et al ). Where a mixed species assemblage of birds is being surveyed, interspecific attraction to the calls of a single species may be exploited.…”
Section: Candidate Set Of Models Provided By Mitchell and Donovan () mentioning
confidence: 99%